A Dirty Little Secret - Gillian Judson (Journal of the Scholarship of Teaching and Learning, 2023)
This article describes my tumultuous journey studying imagination in a graduate leadership seminar using an arts-based pedagogy called Performative Inquiry. Focusing on my own teaching and learning in this course, I share insights that inform my future teaching and can support colleagues interested in exploring imagination with their students. I accepted risks associated with arts-based performances and entered a shared space of vulnerability with my students. My struggles with resistance were real, and so too was the realization of the important role vulnerability plays in imagination-focused (leadership) education. I suggest that Performative Inquiry offers other (leadership) educators a powerful pedagogy and methodology for understanding imagination in their own lives and inquiring into their leadership education practices. Arts-based practices allow learners to feel their own imaginations and experience possibility by accepting invitations to be vulnerable, performing learning in a range of productive and generative ways.